2013
DOI: 10.1111/cen.12089
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex steroids, intrahepatic fat and liver enzymes in the association between SHBG and metabolic features

Abstract: The significant association between SHBG and fasting glycaemia, HbA1c and lipid levels in dysmetabolic men was not related to either sex hormones or markers of liver function, but was dependent on intrahepatic fat. This suggests that intrahepatic fat, but not alterations in liver function markers, may be involved in the association between SHBG and glucose and lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
3
26
1
Order By: Relevance
“…In this study, the association between sex steroids and WC was not significant (data not shown) that may suggest that this clinical parameter would not be suitable. In a previous study of dysmetabolic subjects, we found that SHBG level correlated inversely with glucose and lipids levels but that this relationship depended on the intrahepatic fat content, which we did not measure in the present study [36]. Moreover, in our current study, SHBG concentrations correlated inversely with BMI and SBP, and this confirmed the data of previous studies of different ethnic populations [32,37].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the association between sex steroids and WC was not significant (data not shown) that may suggest that this clinical parameter would not be suitable. In a previous study of dysmetabolic subjects, we found that SHBG level correlated inversely with glucose and lipids levels but that this relationship depended on the intrahepatic fat content, which we did not measure in the present study [36]. Moreover, in our current study, SHBG concentrations correlated inversely with BMI and SBP, and this confirmed the data of previous studies of different ethnic populations [32,37].…”
Section: Discussionsupporting
confidence: 90%
“…Mendelian randomisation studies, which are less likely to be confounded than traditional observational studies, have associated low SHBG (Ding et al 2009) but not testosterone (Haring et al 2013) with an increased risk of future diabetes. In cross-sectional studies of men with (Grossmann et al 2008) and without (Bonnet et al 2013) diabetes, SHBG but not testosterone was inversely associated with worse glycaemic control. SHBG may have biological actions beyond serving as a carrier protein for and regulator of circulating sex steroids (Wallace et al 2013).…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 86%
“…We also found female-specific changes in ADIPO, GLCE, FETUB and SHBG, which all have functions related to lipid biosynthesis or metabolism [31-34]. In addition to its role in lipid-related pathways, SHBG also serves as the main transport protein for sex steroids such as oestrogen and testosterone [35].…”
Section: Discussionmentioning
confidence: 99%